LAP proteins are localized at the post‐synaptic membrane of neuromuscular junctions and appear to modulate synaptic morphology and transmission. Issue 3 (28th July 2016) - Kravic, Bojana; Huraskin, Danyil; Frick, Alexander D.; Jung, Jasmin; Redai, Veronika; Palmisano, Ralf; Marchetto, Sylvie; Borg, Jean‐Paul; Mei, Lin; Hashemolhosseini, Said
Abstract: Erbin, Lano, Scribble, and Densin‐180 belong to LAP (leucine‐rich repeats and PDZ domain) adaptor proteins involved in cell signaling pathways. Previously, we identified Erbin, Lano, and Scribble, but not Densin‐180, in muscle cells, where they are involved in regulating the aggregation of nicotinic acetylcholine receptors in vitro . Here, we analyzed their cellular localization at the neuromuscular junction (NMJ) in skeletal muscles of mice. Erbin, Lano, and Scribble were significantly accumulated at NMJs and localized in different synaptic cells. Moreover, we used mouse mutants to analyze the role of Erbin at the NMJ. We used two Erbin mutant mouse strains that either completely lack Erbin protein (Erbin null/null ) or express a truncated Erbin mutant where the carboxy‐terminal PDZ domain is replaced by β‐galactosidase (Erbin ΔC/ΔC ) thereby abolishing its interaction with ErbB receptor tyrosine kinases. Neither the lack of the PDZ domain of Erbin, nor its complete absence interfered with the general localization of LAP proteins at NMJs, but Lano and Scribble transcript levels were up‐regulated in homozygous Erbin‐null muscles. Furthermore, grip strength was reduced and neural transmission impaired in homozygous aged Erbin‐null but not Erbin‐ΔC mice. Erbin‐null skeletal muscles did not reveal any conspicuous impairment of the muscle fiber. Localization of other NMJ marker proteins was not affected either. Quantitative 3D morphometry showed that NMJs of Erbin‐null muscles were significantly smaller and fragmented in the soleus. We speculate that Erbin, Lano, and Scribble act at the post‐synaptic membrane of NMJs in a concerted fashion to regulate nicotinic acetylcholine receptors cluster morphology and neural transmission. Cover Image for this issue: doi:10.1111/jnc.13340 . Abstract : LAP proteins [leucine‐rich repeats (LRRs) and PDZ domain] Erbin, Lano, and Scribble are expressed by different entities at neuromuscular junctions of mice. Erbin is expressed by myelinating Schwann cells, Erbin and Lano by terminal Schwann cells, Lano and Scribble by motor neurons, and all three by the muscle fiber. Moreover, Erbin, Lano, and Scribble are involved in proper aggregation of neurotransmitter receptors (AChRs) at NMJs. Cover Image for this issue: doi:10.1111/jnc.13340 .